Effective Utilization of NIR Wavelengths for Photo‐Controlled Polymerization: Penetration Through Thick Barriers and Parallel Solar Syntheses. (12th December 2019) - Wu, Zilong; Jung, Kenward; Boyer, Cyrille
Abstract: This contribution details an efficient and controlled photopolymerization regulated by far‐red ( λ =680 nm) and NIR ( λ =780 and 850 nm) light in the presence of aluminium phthalocyanine and aluminium naphthalocyanine. Initiating radicals are generated by photosensitization of peroxides affording an effective strategy that provides controlled polymerization of a variety of monomers with excellent living characteristics. Critically, long wavelength irradiation provides penetration through thick barriers, affording unprecedented rates of controlled polymerization that can open new and exciting applications. Furthermore, a more optimized approach to performing solar syntheses is presented. By combining the narrow Q‐bands of these photocatalysts with others possessing complementary absorptions, layered, independent polymerizations and organic transformations may be performed in parallel under a single broadband emission source, such as sunlight. Abstract : Der Sonne entgegen : Eine effiziente, durch Rot‐ und NIR‐Licht vermittelte RAFT‐Photopolymerisation mit Phthalocyaninen als Photosensibilisatoren wird vorgestellt. Die Anwendung längerer Wellenlängen erlaubt Polymerisation mittels Bestrahlung durch Barrieren. Photochemie bei langen Wellenlängen könnte gemeinsam mit bestehenden Photokatalysatoren eingesetzt werden, um die Nutzung von Sonnenlicht für chemische Synthesen zu optimieren.